ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU DENGAN METODE ECONOMIC ORDER QUANTITY DAN ECONOMIC PRODUCTION QUANTITY PADA BROWNIES CINTA DI KARANGANYAR - Astri Remasari; Yohanes Djoko Suseno; Sunarso Sunarso (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
Brownies Cinta is one of the companies engaged in the food processing industry which is located at Jl. Muwardi, East Cangakan, Cangakan, Karanganyar. In food industry companies, the production process is very important because it affects the survival of the company. The purpose of this study is to analyze the efficiency of raw material inventory control using the Economic Order Quantity and Economic Production Quantity methods. The results of the analysis of inventory control of Brownies Cinta raw materials obtained the following conclusions: With the EOQ method, the results of inventory costs are Rp 9,812,035. With the EPQ method the total annual costs are Rp 8,493,009. Compared to the EOQ and EPQ methods it can be seen that the EPQ method is more able to minimize costs compared to the EOQ method with a difference of Rp 1,319,026.